Constant temperature response factors for fast calculation of sparse BHE field g-functions. (February 2019) - Fossa, Marco; Priarone, Antonella
Abstract: Ground Coupled Heat Pumps (GCHP) are efficient heating systems which mainly rely on the correct design of their ground heat exchangers for attaining the best performance. Such design process is often based on a ground response model which involves the solution of the transient conduction equation. A successful calculation technique for ground response predictions is based on basic thermal response factors also known as g-functions. These solutions can be built according to different boundary conditions and eventually taking into account the variation of the heat rate along the vertical borehole heat exchanger (BHE). The present paper describes a new technique for generating temperature response factors for different BHE field geometries by interrogating a table which provides temperature excess values at different dimensionless distances and times from a single, constant temperature, finite length heat source. In spite this method is not completely suitable for calculating the g-functions of densely packed BHE field in the late period, it is demonstrated that the present procedure is very fast and reliable for calculating the temperature response factors in medium time horizons (e.g. the 10 year deadline of the Ashrae Method) or even in the asymptotic time region of sparse BHE fields. Highlights: A FEM based numerical model is employed for calculating the Temperature Response Factors (TRFs) around a finite cylindrical heat source (FCS). Numerical results are provided in form of a Table for spline interpolation and superposition in order to generate TRFs. A large amount of g-functions have been calculated and compared with reference to BC-III solutions. Very good agreement for sparse borefields (open configurations and in-line) has been obtained with reference to literature data. For rectangular and square packed configurations, reliable estimations (average error 8%) for time horizons up to 10 years have been obtained.